Foundations in cancer research. The turns of life and science - Svoboda, Jan (Advances in cancer research, 2008)
This chapter provides a personal insight into the scientific and social atmosphere in former Czechoslovakia. It covers the period of the rise of Hasek's immunologic school and application of immunologic tolerance to Rous sarcoma virus (RSV) heterotransmission. These approaches permitted establishment of a new model of mammalian cells transformed by RSV (virogenic XC cells), where the noninfectious viral genome was kept indefinitely as new genetic information (provirus). RSV was rescued from nonpermissive mammalian cells by fusion (complementation) with permissive chicken fibroblasts; this opened the way to understanding virus nonpermissiveness. Mammalian cells transformed by the reverse transcript of v-src mRNA were characterized, and the resulting provirus was shown to be highly oncogenic for chickens and to carry tumor-specific transplantation antigen. Other areas covering epigenetic reversion of RSV-transformed cells and long-term persistence of chicken leucosis viruses in foreign avian species are discussed.
Keywords: Research; Oncogenic Viruses; Rous sarcoma virus; virová transformace buněk; výzkum; dějiny 20. století; History, 20th Century; zvířata; Genes, src; Československo; Cell Transformation, Viral; lékařská onkologie; virus Rousova sarkomu; Czechoslovakia; integrace viru; Virus Integration; Animals; geny src; onkogenní viry; Medical Oncology